HUMAN DEFICIENCY IN THE AGRO-INDUSTRIAL COMPLEX OF THE REPUBLIC OF SAKHA (YAKUTIA): WAYS TO SOLVE THE PROBLEMS - K. Togonokhov; К. Тогонохов Х. (VESTNIK UNIVERSITETA, 2018)
This article deals with the problem of the personnel supply of the agro-industrial complex of the Republic of Sakha (Yakutia), caused by low conditions and quality of life in rural areas. The conducted research made it possible to identify the main problems of the personnel deficit in the agro-industrial complex under the conditions of Russia’s innovative economy, and also to identify the main reasons that hamper the employment of young specialists in rural areas. Particular attention is paid to the problem of training, professional development and professional training of specialists in the field of agroindustrial complex. Recommendations are proposed for the elimination of the personnel shortage and the formation of competitive personnel in the agro-industrial complex. Рассмотрена проблема кадрового обеспечения агропромышленного комплекса Республики Саха (Якутия), вызванное низкими условиями и качеством жизни в сельской местности. Проведенное исследование позволило определить основные проблемы кадрового дефицита в агропромышленном комплексе в условиях инновационной экономики России, а также выявить основные причины, препятствующие трудоустройству молодых специалистов в сельской местности. Особое внимание уделено проблеме подготовки, повышения квалификации и профессионального обучения специалистов в области агропромышленного комплекса. Предложены рекомендации по устранению кадрового дефицита и формированию конкурентоспособных кадров в агропромышленном комплексе.